Analisis Respon Dinamis dan Distorsi Harmonisa pada Inverter NPC Satu Fasa Menggunakan Multicarrier PWM - I Ketut Wiryajati; Ida Ayu Sri Adnyani; I Ketut Perdana Putra; I G A K Chatur Adhi Wirya Aryadi (MES Bogor, 2026)
This study presents the performance analysis of a single-phase Neutral Point Clamped (NPC) inverter using the multicarrier pulse width modulation (PWM) technique based on MATLAB/Simulink simulation. The inverter system employs eight semiconductor switches controlled through multilevel PWM modulation to produce an AC output waveform close to sinusoidal characteristics. Performance evaluation was conducted through statistical analysis of output voltage and current, transient response, dynamic response, and harmonic distortion analysis. The simulation results show that the inverter produces relatively stable voltage and current waveforms with symmetrical characteristics between positive and negative cycles. The output voltage achieved a maximum value of 45.86 V with an RMS value of 31.02 V. The system also demonstrated a relatively fast dynamic response with rise time and fall time values of 3.768 ms. However, FFT analysis indicated that the Total Harmonic Distortion (THD) remained relatively high at 42.93%. Therefore, optimization of switching frequency, control methods, and LC filter design is required to improve power quality performance.